Penghasilan modul pembelajaran bahan kejuruteraan awam bagi kursus Ijazah Sarjana Muda Kejuruteraan Awam, Kolej Universiti Teknologi Tun Hussein Onn - Ramli, Liza Suhana (2003)
The purpose of this research is to develop a learning module for Material of Civil Engineering subject to fulfill the student's requirement Questionnaire forms was used as the instruments throughout this research Respondents involved in this research are the student who leam Material of Civil Engineering subject (BKA 2612) for their Bachelor Degree in Civil Engineering. Data has been analyzed by using descriptive analysis using SPSS software. The result from the analysis reveal that the content, user friendliness and feasibility of this module does fulfill the student's need in understanding this subject. To further improve the quality of this module, it is recommended for those involved to make an enhancement to the module in order to improve student's interest and their achievement in Material of Civil Engineering subject.